If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-62x=-18
We move all terms to the left:
6x-62x-(-18)=0
We add all the numbers together, and all the variables
-56x+18=0
We move all terms containing x to the left, all other terms to the right
-56x=-18
x=-18/-56
x=9/28
| -9.4=c-8.3 | | 3=x/8-5 | | 2(x-9)-5=-7(-3x+4)-9x | | 21+6s=81 | | 1404-70x=12500 | | -5x+6-4x=-66 | | (9x-5)=(7x+7) | | -12g=12.6 | | 12(x-3)=24x | | 7c^2-26c+15=0 | | 7.1=c+1 | | 7+7a=3(1+a)-4 | | 2x+9+3x+x=1 | | m+7=25;m= | | -7c-12=3c+8 | | 1/y+2=2/y+3-3/y^2+5y+6 | | -6y+40=8(y-9) | | c-5.5=-2.8 | | 7x+9+x+10=17 | | -10=2x+3x+5 | | X^2+y^2-12y=-20 | | 11y-20=90 | | -4x+2x=-5-x | | 3/6x-5x/10x3=4/x^2 | | X^2+y^2-12y=-12 | | -5-x=-2x | | 3(x+7)=6)x+2) | | -1/3r=-1/4 | | 1/4f=11/3 | | 6/14=7/b-3 | | 4/3*x=84 | | 1/4f=32/3 |